2017
DOI: 10.24193/subbbiol.2017.2.09
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth response and nitrate reductase activities of roots of Chromolaena odorata in a model spent lubricating oil-polluted soil

Abstract: SUMMARY.The ability of Chromolaena odorata propagated by stem cuttings and grown for 50 days in the soil containing five (5) different concentrations of spent lubricating oil (SLO) in soil (0, 1, 3, 6, 9 and 12 % SLO), was investigated. The experiments were watered daily at 70% moisture field capacity. Parameters such as number leaves per plant, shoot length, plant height as well as nitrate reductase activities were measured. Shoot length as well as leaf number were significantly (p < 0.05) reduced, compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Erhenhi and Ikhajiagbe (2012) have observed that oil has a multitude of phytotoxic effects on plant growth and development, thus resulting in massive agricultural and economic losses in contaminated areas. Other researchers (Vwioko and Fashemi, 2005;Anoliefo et al, 2017;Ikhajiagbe et al, 2017) have reported that petroleum hydrocarbons are hazardous to both plants and mammals. The presence of oil in the soil is a major environmental concern as it creates unfavorable conditions for plant growth, most commonly due to insufficient soil aeration.…”
Section: Introductionmentioning
confidence: 96%
“…Erhenhi and Ikhajiagbe (2012) have observed that oil has a multitude of phytotoxic effects on plant growth and development, thus resulting in massive agricultural and economic losses in contaminated areas. Other researchers (Vwioko and Fashemi, 2005;Anoliefo et al, 2017;Ikhajiagbe et al, 2017) have reported that petroleum hydrocarbons are hazardous to both plants and mammals. The presence of oil in the soil is a major environmental concern as it creates unfavorable conditions for plant growth, most commonly due to insufficient soil aeration.…”
Section: Introductionmentioning
confidence: 96%